Peroxisome Dynamics: Molecular Players, Mechanisms, and (Dys)functions. (14th November 2012) - Fransen, Marc
Abstract : Peroxisomes are remarkably versatile cell organelles whose size, shape, number, and protein content can vary greatly depending on the organism, the developmental stage of the organism's life cycle, and the environment in which the organism lives. The main functions usually associated with peroxisomes include the metabolism of lipids and reactive oxygen species. However, in recent years, it has become clear that these organelles may also act as intracellular signaling platforms that mediate developmental decisions by modulating extraperoxisomal concentrations of several second messengers. To fulfill their functions, peroxisomes physically and functionally interact with other cell organelles, including mitochondria and the endoplasmic reticulum. Defects in peroxisome dynamics can lead to organelle dysfunction and have been associated with various human disorders. The purpose of this paper is to thoroughly summarize and discuss the current concepts underlying peroxisome formation, multiplication, and degradation. In addition, this paper will briefly highlight what is known about the interplay between peroxisomes and other cell organelles and explore the physiological and pathological implications of this interorganellar crosstalk.